Preparation method and application of polyzirconium chloride-sodium alginate composite coagulant
By polymerizing and combining zirconium chloride with sodium alginate, a polymerized zirconium chloride-sodium alginate composite coagulant was prepared, which solved the lack of biological toxicity, stability and water purification capacity of existing composite zirconium salt coagulant. The problem has achieved efficient and safe water purification effect.
Patent Information
- Application Number
- CN202310277996.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-03-21
AI Technical Summary
The existing composite zirconium salt coagulants have problems of biological toxicity, poor stability and insufficient water purification capacity.
By polymerizing and combining zirconium chloride with sodium alginate, a polymerized zirconium chloride-sodium alginate composite coagulant is prepared. The composite coagulant has the characteristics of good stability, excellent water purification ability and no biological toxicity.
It realizes efficient water purification, avoids the occurrence of biological toxicity, and improves the stability and application range of coagulants.
Smart Images

Figure BDA0004137006770000091 
Figure BDA0004137006770000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a preparation method and application of a polyzirconium chloride-sodium alginate composite coagulant. Background Art
[0002] Water is a necessary condition for the survival of living things. In recent years, the world's environmental problems have become increasingly prominent, among which water pollution has become increasingly serious.
[0003] In order to solve the problem of water pollution, people have developed water treatment methods based on physics, chemistry and biology. Coagulation is to add coagulants to sewage to aggregate and settle pollutants in the water, so that solid floccules can be removed from the wastewater. As a chemical treatment method, the key to coagulation is the selection of coagulant types. Coagulants are usually divided into inorganic coagulants and organic coagulants, single coagulants and composite coagulants.
[0004] At present, coagulation is widely used due to its low treatment cost and high efficiency. The most commonly used coagulants include conventional aluminum or iron salts, polyaluminum chloride, polyferric sulfate and polyacrylamide. However, the residual aluminum and residual monomers released by polyaluminum chloride in wastewater are toxic to microorganisms, animals and plants. When iron salt coagulants are used to treat wastewater, the effluent has a high chromaticity, and the high residual iron ion content will lead to a low pH value of the drainage, which is corrosive to pipes and equipment.
[0005] Compared with traditional coagulants, zirconium salt coagulants have received more attention due to their larger floc size, more compact flocs, better sedimentation performance, and good biocompatibility of zirconium. The composition of sewage is often complex and diverse, and a single coagulant is difficult to meet the requirements of coagulation effluent. Composite coagulants are often used to deal with the complexity and diversity of sewage components. Existing composite zirconium salt coagulants are mainly inorganic composite zirconium salt coagulants, such as polysilicic acid-polyzirconium chloride and polyaluminum zirconium silicate. However, polyaluminum zirconium silicate will have biological toxicity problems caused by residual aluminum ions. Polysilicate polyzirconium chloride has poor stability and is not easy to preserve. At the same time, due to the complex components of polysilicic acid, it will affect the hydrolysis and polymerization of zirconium solution.
[0006] Therefore, there is an urgent need to develop a green and efficient composite coagulant to improve the water purification effect and solve the biological toxicity and stability problems of existing composite coagulants. Summary of the invention
[0007] The existing composite zirconium salt coagulants have problems of biological toxicity, poor stability and poor water purification ability. In order to solve the above technical problems, the present invention provides a method for preparing a polyzirconium chloride-sodium alginate composite coagulant. The present invention polymerizes and composites zirconium chloride and sodium alginate to prepare a polyzirconium chloride-sodium alginate composite coagulant with good stability and excellent coagulation and water purification ability. At the same time, the composite coagulant does not have the problem of biological toxicity and will not cause secondary pollution.
[0008] The specific technical scheme of the present invention is:
[0009] On the one hand, the present invention provides a method for preparing a polyzirconium chloride-sodium alginate composite coagulant, comprising the following steps:
[0010] (1) dissolving sodium alginate in water to obtain a sodium alginate solution;
[0011] (2) dissolving zirconium chloride in water to obtain a zirconium chloride solution, adding the alkali solution dropwise by a trace alkali method, and stirring until the precipitate is completely dissolved to obtain a polyzirconium chloride solution;
[0012] (3) adding the sodium alginate solution obtained in step (1) to the polyzirconium chloride solution in step (3) under stirring conditions, stirring continuously, and aging to obtain a polyzirconium chloride-sodium alginate composite coagulant;
[0013] In the polyzirconium chloride-sodium alginate composite coagulant, the mass ratio of zirconium to sodium alginate is (1-10):1.
[0014] As zirconium salt coagulants are gradually gaining attention as a new type of efficient and non-toxic coagulant, the present invention intends to compound green organic matter with zirconium salts to achieve the purpose in order to provide a stable, excellent water purification and non-biologically toxic green environmentally friendly composite coagulant. Sodium alginate is a polysaccharide extracted from kelp or sargassum of brown algae, and its molecules are full of hydroxyl and carboxyl groups. The present invention successfully prepares a polyzirconium chloride-sodium alginate composite coagulant by polymerizing and compounding zirconium chloride and sodium alginate. The polyzirconium chloride-sodium alginate composite coagulant has the characteristics of good stability, excellent coagulation and water purification ability, and good biocompatibility.
[0015] In the selection of green organic matter of the present invention, in addition to the requirement for good biocompatibility, the structure of the organic matter is also greatly restricted. First of all, the molecular structure of the organic matter needs to be able to form a strong molecular binding force with the zirconium salt molecules. Therefore, the molecular structure of the ideal material selection of the organic matter should be full of electron-donating groups, and a stable composite structure is formed by the strong interaction between the electron-donating groups and the zirconium salt cations. However, the composite structure formed between chemical molecules, the process and mechanism of forming the composite structure are complex and diverse, and it is also unknown whether the properties of the formed composite structure have changed compared to the original molecule. For example, if chitosan is selected as a green organic material, and chitosan is compounded with zirconium salt molecules to form a composite coagulant, the coagulation effect is greatly reduced. The research team of the present invention found that the polyzirconium chloride-sodium alginate composite coagulant obtained by polymerizing and compounding sodium alginate and zirconium chloride has a good water purification effect.
[0016] In the preparation method of the polyzirconium chloride-sodium alginate composite coagulant, a polyzirconium chloride solution and a sodium alginate solution are mixed and reacted to prepare a polyzirconium chloride-sodium alginate composite coagulant. In this process, zirconium ions coordinate and chelate with hydroxyl and carboxyl groups on sodium alginate, and hydroxyl groups in polyzirconium chloride react with carbon groups in sodium alginate, so that the molecular chain network of zirconium-containing molecules continues to grow and expand. Therefore, when the polyzirconium chloride-sodium alginate composite coagulant is used for coagulation treatment of wastewater, the adsorption bridging and net capture effects between suspended colloids are enhanced. At the same time, a polyzirconium chloride-sodium alginate composite coagulant with a large molecular chain network and a large molecular weight is easier to settle.
[0017] In the polyzirconium chloride-sodium alginate composite coagulant, the mass ratio of zirconium to sodium alginate is (1-10):1.
[0018] In the polyzirconium chloride-sodium alginate composite coagulant prepared by the preparation method provided by the present invention, the mass ratio of zirconium to sodium alginate should be in the range of (1-9): 1. If the zirconium content is too much, the obtained polyzirconium chloride-sodium alginate composite coagulant has a small and unstable structural network and poor flocculation ability; if the zirconium content is too little, in the obtained polyzirconium chloride-sodium alginate composite coagulant, part of the zirconium cations are embedded in the sodium alginate molecules, which is not conducive to the adsorption of impurities by the zirconium cations and reduces the flocculation ability.
[0019] In the preparation method of the polyzirconium chloride-sodium alginate composite coagulant provided by the present invention, as a preferred embodiment of the above technical solution of the present invention, specifically:
[0020] The concentration of the sodium alginate solution prepared in step (1) needs to be limited to 4-10wt%. If the concentration of the sodium alginate solution is too low, the size of the obtained polyzirconium chloride-sodium alginate composite coagulant structure network will be small and unstable, and the flocculation ability will be poor. If the concentration of the sodium alginate solution is too high, the zirconium cations in the obtained polyzirconium chloride-sodium alginate composite coagulant structure will be unevenly distributed, and some zirconium cations will be embedded in the sodium alginate molecules, which is not conducive to the adsorption of impurities by the zirconium cations, and the flocculation ability will be reduced.
[0021] The alkalinity of the polyzirconium chloride solution in step (2) should be in the range of 0 to 2.5. Different alkalinity will lead to different hydrolysis of zirconium ions, the existence form and the existence ratio of zirconium ions. The polyzirconium chloride-sodium alginate composite coagulant obtained by compounding the polyzirconium chloride solution with the sodium alginate solution has good coagulation ability when the alkalinity of the polyzirconium chloride solution is in the range of 0 to 2.5.
[0022] As a preferred embodiment of the above technical solution of the present invention, in step (2), the concentration of the zirconium chloride solution is 10-20%.
[0023] As a preferred embodiment of the above technical solution of the present invention, in step (2), the alkaline solution is a sodium hydroxide solution. Preferably, the concentration of the sodium hydroxide solution is 70 to 80 g / L.
[0024] As a preferred embodiment of the above technical solution of the present invention, in step (2), the stirring rate is 200-300 rpm.
[0025] As a preferred embodiment of the above technical solution of the present invention, in step (3), the continuous stirring rate is 200 to 500 rpm.
[0026] As a preferred embodiment of the above technical solution of the present invention, in step (3), the continuous stirring time is 12 to 24 hours.
[0027] As a preferred embodiment of the above technical solution of the present invention, in step (3), the aging method is standing. Preferably, the standing time is not less than 18 hours.
[0028] On the other hand, the present invention provides the use of the above-mentioned polyzirconium chloride-sodium alginate composite coagulant in coagulation treatment.
[0029] Preferably, when the polyzirconium chloride-sodium alginate composite coagulant is used in coagulation treatment, the conditions are: the dosage is 10-100 mg / L, and the pH range is 4-9.
[0030] The calculation method of "basicity" mentioned in the present invention is: basicity = [OH - ] / [Zr 4+ ].
[0031] Compared with the prior art, the present invention has the following technical effects:
[0032] (1) The present invention uses sodium alginate and zirconium chloride as raw materials, mixes sodium alginate solution with polyzirconium chloride solution for grafting, and obtains polyzirconium chloride-sodium alginate composite coagulant. The preparation method of the composite coagulant provided by the present invention has the advantages of being simple, easy to operate, quick and convenient, etc.
[0033] (2) The polyzirconium chloride-sodium alginate composite coagulant prepared by the preparation method provided by the present invention has the characteristics of high molecular weight and high charge density, and can generate high-charge cations. Compared with traditional coagulants, such as aluminum salts and iron salts, it has stronger electrical neutralization ability and flocculation ability.
[0034] (3) The polyzirconium chloride-sodium alginate composite coagulant prepared by the preparation method provided by the present invention has strong net capturing and bridging capabilities and a wide pH adaptability range, so it has a wider application range than existing coagulants.
[0035] (4) The polyzirconium chloride-sodium alginate composite coagulant prepared by the preparation method provided by the present invention has good biocompatibility, is green and healthy, and will not cause secondary pollution. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0039] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0040] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:1.
[0041] Example 2
[0042] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0043] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0044] (3) Under stirring at 500 rpm, 16.66 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, and stirring was continued. The solution was reacted for 12 h, allowed to stand for 26 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 3:1.
[0045] Example 3
[0046] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0047] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 200 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0048] (3) Under stirring at 200 rpm, 8.33 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, and stirring was continued. The solution was reacted for 20 h, allowed to stand for 20 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 6:1.
[0049] Example 4
[0050] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0051] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0052] (3) Under stirring at 500 rpm, 5.55 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, and stirring was continued. The solution was reacted for 24 h, allowed to stand for 18 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 9:1.
[0053] Example 5
[0054] (1) Weigh 0.6 g of sodium alginate, add the weighed sodium alginate into 70 ml of deionized water while heating in a water bath at 50°C and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 6 g / L sodium alginate solution.
[0055] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0056] (3) Under stirring at 500 rpm, 83.33 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, and stirring was continued. The mixture was reacted for 12 h, allowed to stand for 24 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 1:1.
[0057] Example 6
[0058] (1) Weigh 0.4 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water while heating in a water bath at 50°C and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 4 g / L sodium alginate solution.
[0059] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0060] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 4 ml of polyzirconium chloride solution, and stirring was continued. The solution was reacted for 12 h, allowed to stand for 24 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 1:1.
[0061] Example 7
[0062] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0063] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 2.14 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 2.0.
[0064] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:1.
[0065] Example 8
[0066] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0067] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 2.68 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 2.5.
[0068] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:1.
[0069] Comparative Example 1 (the main difference from Example 1 is that in the obtained polyzirconium chloride-sodium alginate composite coagulant, the mass ratio of zirconium:sodium alginate is 0.5:1)
[0070] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0071] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0072] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 5 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:2.
[0073] Comparative Example 2 (the main difference from Example 1 is that the mass ratio of zirconium to sodium alginate in the obtained polyzirconium chloride-sodium alginate composite coagulant is 12:1)
[0074] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0075] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0076] (3) Under stirring at 500 rpm, 4.17 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, and stirring was continued. The solution was reacted for 12 h, allowed to stand for 24 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 12:1.
[0077] Comparative Example 3 (the main difference from Example 1 is that the concentration of sodium alginate used in preparing the polyzirconium chloride-sodium alginate composite coagulant is 15 g / L)
[0078] (1) Weigh 1.5 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 15 g / L sodium alginate solution.
[0079] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0080] (3) Under stirring at 500 rpm, 33.33 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, and stirring was continued. The solution was reacted for 12 h, allowed to stand for 24 h, and then the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant with a mass ratio of zirconium to sodium alginate of 1:1.
[0081] Comparative Example 4 (the main difference from Example 1 is that the concentration of sodium alginate used in preparing the polyzirconium chloride-sodium alginate composite coagulant is 2 g / L)
[0082] (1) Weigh 0.2 g of sodium alginate, add the weighed sodium alginate into 70 ml of deionized water while heating in a water bath at 50°C and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 2 g / L sodium alginate solution.
[0083] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0084] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 2 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:1.
[0085] Comparative Example 5 (the main difference from Example 1 is that the alkalinity of the polyzirconium chloride solution used in preparing the polyzirconium chloride-sodium alginate composite coagulant is 3.0)
[0086] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0087] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 3.22 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 3.0.
[0088] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:1.
[0089] Comparative Example 6 (the main difference from Example 1 is that the alkalinity of the polyzirconium chloride solution used in preparing the polyzirconium chloride-sodium alginate composite coagulant is 0)
[0090] (1) Weigh 1.0 g of sodium alginate, add the weighed sodium alginate to 70 ml of deionized water under heating at 50°C in a water bath and stirring at 100 rpm, stir continuously for 1 h, and dilute to a 100 ml volumetric flask to obtain a 10 g / L sodium alginate solution.
[0091] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; take 50 ml of the zirconium chloride solution, stir at 300 rpm for 2 h, do not add sodium hydroxide solution, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 0.
[0092] (3) Under stirring at 500 rpm, 50 ml of sodium alginate solution was added to 10 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-sodium alginate composite coagulant having a mass ratio of zirconium to sodium alginate of 1:1.
[0093] Comparative Example 7 (the main difference from Example 1 is that no sodium alginate is compounded)
[0094] Weigh 10g of ZrCl4 powder, add the weighed ZrCl4 powder into 70ml of deionized water while stirring at 300rpm, stir continuously for 0.5h, dilute to volume in a 100ml volumetric flask to obtain a uniform 100g / L zirconium chloride solution; prepare 80g / L sodium hydroxide solution, take 1.07ml of sodium hydroxide solution, slowly add it dropwise to the prepared 50ml zirconium chloride solution, and react for 2h while stirring at 300rpm, dilute to volume with a 100ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0, i.e., a zirconium salt coagulant.
[0095] Comparative Example 8 (the main difference from Example 1 is that sodium alginate is replaced by chitosan)
[0096] (1) Weigh 0.2 g of chitosan, add 60 ml of acetic acid solution (volume fraction 1%), stir continuously at 100 rpm for 1 h, and then make the volume to 100 ml with acetic acid solution to obtain a 2 g / L chitosan solution.
[0097] (2) Weigh 10 g of ZrCl4 powder, add the weighed ZrCl4 powder to 70 ml of deionized water while stirring at 300 rpm, stir continuously for 0.5 h, and dilute to volume in a 100 ml volumetric flask to obtain a uniform 100 g / L zirconium chloride solution; prepare 80 g / L sodium hydroxide solution, take 1.07 ml of the sodium hydroxide solution, slowly add it dropwise to the prepared 50 ml zirconium chloride solution, and react for 2 h while stirring at 300 rpm, and dilute to volume with a 100 ml volumetric flask to obtain a polyzirconium chloride solution with an alkalinity of 1.0.
[0098] (3) Under stirring at 500 rpm, 50 ml of chitosan solution was added to 2 ml of polyzirconium chloride solution, stirring was continued, the solution was reacted for 12 h, and allowed to stand for 24 h. Then, the volume was fixed with a 100 ml volumetric flask to obtain a polyzirconium chloride-chitosan composite coagulant with a mass ratio of zirconium to chitosan of 1:1.
[0099] Performance Evaluation
[0100] (1) The polyzirconium chloride-sodium alginate composite coagulants prepared in Examples 1-8 and Comparative Examples 1-6, the zirconium salt coagulant obtained in Comparative Example 7, and the polyzirconium chloride-chitosan composite coagulant obtained in Comparative Example 8 were respectively used to treat wastewater from a food factory in Huzhou City. The COD of the wastewater was 3821.52 mg / L, the TP was 76.23 mg / L, and the pH was 6.64.
[0101] Take 16 500ml measuring cylinders, add 400ml of the above wastewater respectively, add the polyzirconium chloride-sodium alginate composite coagulant prepared in Examples 1-8 and Comparative Examples 1-6, the zirconium salt coagulant obtained in Comparative Example 7, and the polyzirconium chloride-chitosan composite coagulant obtained in Comparative Example 8, stir at 400rpm for 8min, then stir at 50rpm for 3min, stand for 20min, take the supernatant, and measure the COD and TP content after treatment. The results are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] As can be seen from Table 1, the polyzirconium chloride-sodium alginate composite coagulants prepared in Examples 1-8 have better COD and TP removal efficiencies. The polyzirconium chloride-sodium alginate composite coagulants prepared in Examples 1-8 have a TP treatment efficiency of more than 90%. Compared with Comparative Example 7, the TP treatment efficiency of polyzirconium chloride and sodium alginate after composite is improved.
[0106] It can be seen from the comparison between Comparative Example 1 and Comparative Example 2 and Example 1 that in the polyzirconium chloride-sodium alginate composite coagulant provided by the present invention, the mass ratio of zirconium to sodium alginate should be within an appropriate range. Too much or too little zirconium content will affect its effect in treating wastewater. Further analysis of the reasons: if the zirconium content is too much, the structural network size of the obtained polyzirconium chloride-sodium alginate composite coagulant is small and not firm, and the flocculation ability is poor; if the zirconium content is too little, in the obtained polyzirconium chloride-sodium alginate composite coagulant, part of the zirconium cations are embedded in the sodium alginate molecules, which is not conducive to the adsorption of impurities by the zirconium cations, and the flocculation ability is reduced.
[0107] It can be seen from Comparative Examples 3 and 4 compared with Example 1 that when preparing the polyzirconium chloride-sodium alginate composite coagulant, the sodium alginate concentration used should be within an appropriate range. If the concentration of the sodium alginate solution is too low, the size of the obtained polyzirconium chloride-sodium alginate composite coagulant structure network will be small and not firm, and the flocculation ability will be poor. If the concentration of the sodium alginate solution is too high, the zirconium cations in the obtained polyzirconium chloride-sodium alginate composite coagulant structure will be unevenly distributed, and some zirconium cations will be embedded in the sodium alginate molecules, which is not conducive to the adsorption of impurities by the zirconium cations, and the flocculation ability will be reduced.
[0108] Comparison of Comparative Examples 5 and 6 with Example 1 shows that when preparing the polyzirconium chloride-sodium alginate composite coagulant, the alkalinity of the polyzirconium chloride solution used should be within an appropriate range. In combination with other embodiments and comparative examples, the polyzirconium chloride solution alkalinity is in the range of 1 to 2.5, and the polyzirconium chloride-sodium alginate composite coagulant obtained by compounding with the sodium alginate solution has good coagulation ability.
[0109] It can be seen from the comparison between Comparative Example 7 and Example 1 that after compounding with sodium alginate, the water purification capacity of polyzirconium chloride is improved, which indicates that compounding with sodium alginate is beneficial to improving the flocculation capacity of polyzirconium chloride.
[0110] It can be seen from the comparison between Comparative Example 8 and Example 1 that the water purification capacity of polyzirconium chloride decreases after compounding with chitosan, which indicates that compounding with chitosan is not conducive to the flocculation capacity of polyzirconium chloride.
[0111] (2) The polyzirconium chloride-sodium alginate composite coagulant prepared in Example 1 was applied to the treatment of wastewater from plants 1 to 7 in Huzhou City. The COD of the wastewater from plant 1 was 3722.12 mg / L, the TP was 74.21 mg / L, and the pH was 3.42; the COD of the wastewater from plant 2 was 3827.56 mg / L, the TP was 76.73 mg / L, and the pH was 4.00; the COD of the wastewater from plant 3 was 3836.57 mg / L, the TP was 75.85 mg / L, and the pH was 5.35; the COD of the wastewater from plant 4 was 3821.52 mg / L, The TP is 76.23 mg / L and the pH is 6.64; the COD of the wastewater from Plant No. 5 is 3846.58 mg / L, the TP is 72.23 mg / L and the pH is 7.88; the COD of the wastewater from Plant No. 6 is 3920.62 mg / L, the TP is 75.93 mg / L and the pH is 9.00; the COD of the wastewater from Plant No. 7 is 3941.55 mg / L, the TP is 77.29 mg / L and the pH is 10.14.
[0112] Take 5 500ml measuring cylinders, add 400ml of the above wastewater No. 1-7 respectively, the amount of coagulant added is 60mg / L (calculated as zirconium ion), add 60mg / L (calculated as zirconium ion) of the polyzirconium chloride-sodium alginate composite coagulant prepared in Example 1, stir at 400rpm for 8min, then stir at 50rpm for 3min, let stand for 20min, take the supernatant, and measure the COD and TP content after treatment. The results are shown in Table 2.
[0113] Table 2
[0114] pH COD removal efficiency TP removal efficiency No. 1 3.42 56.16% 87.33% No. 2 4.00 71.43% 92.38% No.3 5.35 67.16% 91.62% No. 4 6.64 65.16% 91.32% No. 5 7.88 68.34% 91.87% No. 6 9.00 65.17% 91.39% No.7 10.14 52.25% 86.37%
[0115] It can be seen from Table 2 that the optimal pH range for the use of the polyzirconium chloride-sodium alginate composite coagulant provided by the present invention is 4-9.
[0116] (3) The polyzirconium chloride-sodium alginate composite coagulant prepared in Example 1 was applied in different dosages to treat wastewater from a food factory in Huzhou City. The COD of the wastewater was 3821.52 mg / L, the TP was 76.23 mg / L, and the pH was 6.64.
[0117] Take 8 500ml measuring cylinders, add 400ml of the above wastewater respectively, and add the polyzirconium chloride-sodium alginate composite coagulant prepared in Example 1 at the dosage of 5, 10, 20, 40, 60, 80, 100, and 120mg / L (calculated as zirconium ions) respectively, stir at 400rpm for 8min, then stir at 50rpm for 3min, let stand for 20min, take the supernatant, and measure the COD and TP content after treatment. The results are shown in Table 3. (Dosage is calculated as zirconium ions, mg / L)
[0118] Table 3
[0119] Dosage COD removal efficiency TP removal efficiency 5 53.21% 89.35% 10 60.43% 90.27% 20 63.23% 91.56% 40 64.58% 94.49% 60 65.16% 91.32% 80 72.36% 92.06% 100 68.95% 91.56% 120 62.65% 89.91%
[0120] It can be seen from Table 3 that the optimal dosage of the polyzirconium chloride-sodium alginate composite coagulant provided by the present invention is 10-100 mg / L.
[0121] It is worth noting that the polyzirconium chloride-sodium alginate composite coagulant prepared by the preparation method provided by the present invention is applied to wastewater treatment of a factory in Huzhou City, but is not limited to the application to wastewater treatment.
[0122] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0123] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a polyzirconium chloride-sodium alginate composite coagulant, characterized in that: The following steps are involved: (1) Dissolving sodium alginate in water to prepare a sodium alginate solution; (2) dissolving zirconium chloride in water to obtain a zirconium chloride solution, adding the alkali solution dropwise by a trace alkali drop method, and stirring until the precipitate is completely dissolved to obtain a polyzirconium chloride solution; (3) adding the sodium alginate solution obtained in step (1) to the polyzirconium chloride solution in step (2) under stirring conditions, stirring continuously, and aging to obtain a polyzirconium chloride-sodium alginate composite coagulant; In the polyzirconium chloride-sodium alginate composite coagulant, the mass ratio of zirconium to sodium alginate is (1-9):1; In step (1), the concentration of the sodium alginate solution is 4-10wt%; In step (2), the alkalinity of the polyzirconium chloride solution is 1.0-2.
5.
2. The method for preparing a polyzirconium chloride-sodium alginate composite coagulant according to claim 1, characterized in that: In step (2), the concentration of the zirconium chloride solution is 10-20%.
3. The method for preparing a polyzirconium chloride-sodium alginate composite coagulant according to claim 1, characterized in that: In step (2), the stirring rate is 200-300 rpm.
4. The method for preparing a polyzirconium chloride-sodium alginate composite coagulant according to claim 1, characterized in that: In step (3), the continuous stirring rate is 200-500 rpm.
5. A method for preparing a polyzirconium chloride-sodium alginate composite coagulant as claimed in claim 1 or 4, characterized in that: In step (3), the continuous stirring time is 12 to 24 hours.
6. The method for preparing a polyzirconium chloride-sodium alginate composite coagulant according to claim 1, characterized in that: In step (3), the aging method is standing, and the standing time is not less than 18 hours.
7. Use of the polyzirconium chloride-sodium alginate composite coagulant prepared by the preparation method according to any one of claims 1 to 6 in coagulation treatment.
8. The use according to claim 7, characterized in that: The application conditions are: dosage is 10~100mg / L, and the pH range is 4~9.
Citation Information
Patent Citations
PAC (polyaluminium chloride)-modified sodium alginate inorganic-organic composite flocculant and preparation method thereof
CN104556331A
Preparation method of polymeric silicic acid polymeric zirconium chloride inorganic high-molecular flocculant
CN108128863A